2022
DOI: 10.31018/jans.v14i4.3912
|View full text |Cite
|
Sign up to set email alerts
|

Dissipation kinetics, decontamination and dietary risk assessment of imidacloprid residue in bitter gourd and soil

Abstract: Imidacloprid is a broad-spectrum neonicotinoid class insecticide with systemic action, widely used on vegetables in India for the management of sucking insect pests. The overall pesticide usage profile in gourds growing districts of Tamil Nadu showed that imidacloprid as the most commonly used insecticide. The present study aimed to develop and validate an analytical approach for detecting imidacloprid and 6-chloronicotinic acid residues in bitter gourd fruit, juice and soil using LC-EI-MS (liquid chromatograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…But however these methods may results in loss of vitamins etc. Suganthi et al [10] stated that the decontamination techniques reduced imidacloprid residues in bitter gourd by 33-80% in 10 days and mentioned minimal risk to consumers, with RQ < 1 after 10 days of imidaclorpid application Naik et al [11] studied the decontamination of imidacloprid from brinjal and okra involving boiling found that the removal up to 96.43% and 73.66% residues from brinjal and okra, respectively. Despite the fact that heat methods are used for decontaminating pesticides in many cases, there is a potential that some vegetables, notably tomato fruit, will lose quality.…”
Section: Introductionmentioning
confidence: 99%
“…But however these methods may results in loss of vitamins etc. Suganthi et al [10] stated that the decontamination techniques reduced imidacloprid residues in bitter gourd by 33-80% in 10 days and mentioned minimal risk to consumers, with RQ < 1 after 10 days of imidaclorpid application Naik et al [11] studied the decontamination of imidacloprid from brinjal and okra involving boiling found that the removal up to 96.43% and 73.66% residues from brinjal and okra, respectively. Despite the fact that heat methods are used for decontaminating pesticides in many cases, there is a potential that some vegetables, notably tomato fruit, will lose quality.…”
Section: Introductionmentioning
confidence: 99%